L’activisme en communication dans la télénovela Órfãos da Terra - Laure Guillot Farneti (Communication)
This article analyzes the Brazilian telenovela Orfãos da Terra in the light of the concept of diversity. The first telenovela focusing on contemporary immigration to Brazil, Orfãos da Terra was broadcast between April 27th and September 2, 2019, under Jair Bolsonaro’s far-right government (2019-2023). Written by Duca Rachid and Thelma Guedes and directed by Gustavo Fernández, it looks at the daily lives of people who have recently immigrated from various parts of the world (Syria, the Democratic Republic of Congo, Haiti, etc.) to the city of São Paulo and who live in a Catholic foster home. Using a semi-discursive analysis of several episodes, this study sheds light on how the TV show presents immigration and the resulting socio-political issues, particularly with respect to discourse and counter-discourse in Brazil.